2020
DOI: 10.1177/1359105320965654
|View full text |Cite
|
Sign up to set email alerts
|

Can ancient and modern stressors be distinguished? A mixed-methods exploration of psychosocial characteristics and health symptoms in young and older adults

Abstract: A novel conceptualisation of stress includes a distinction between ancient (AS) and modern stressors (MS); the notion that established adaptive psychophysiological coping processes may enable individuals to better withstand AS than MS. Two consecutive mixed-methods studies assessed the feasibility of distinguishing between AS and MS in young and older adults, using questionnaires and interviews. MS were positively associated with cold symptoms in older adults; and five psychosocial characteristics were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 35 publications
3
15
2
Order By: Relevance
“…Quantitative analyses of the explicit measures found that AS were associated with coping ability and MS with coping inability. These analyses provided evidence that this group of young to middle‐aged adults coped with a greater total number of AS than MS and that they experienced MS as more stressful than AS, which is consistent with the findings of mixed‐methods studies in younger and older adults (Katsampouris et al., 2020). The concepts of interest in this study were not subject to social acceptability; thus, findings were less likely to have been impacted by issues of self‐representation, social desirability, retrospection, or participant faking and more likely to reveal an explicit association (Fiedler et al., 2006; Gawronski, Hofmann, & Wilbur, 2006; Hofmann, Gawronski, Gschwendner, Le, & Schmitt, 2005; Yoshiuchi et al., 2008).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Quantitative analyses of the explicit measures found that AS were associated with coping ability and MS with coping inability. These analyses provided evidence that this group of young to middle‐aged adults coped with a greater total number of AS than MS and that they experienced MS as more stressful than AS, which is consistent with the findings of mixed‐methods studies in younger and older adults (Katsampouris et al., 2020). The concepts of interest in this study were not subject to social acceptability; thus, findings were less likely to have been impacted by issues of self‐representation, social desirability, retrospection, or participant faking and more likely to reveal an explicit association (Fiedler et al., 2006; Gawronski, Hofmann, & Wilbur, 2006; Hofmann, Gawronski, Gschwendner, Le, & Schmitt, 2005; Yoshiuchi et al., 2008).…”
Section: Discussionsupporting
confidence: 85%
“…Thirty‐eight stimulus images (all coloured, non‐cartoon) for the stressors were selected from a combination of copyright‐free image websites. Thirty‐eight stimulus words for coping were selected from the Oxford English Dictionary and from previous research (Katsampouris et al., 2020). Seven Health Psychology researchers rated the strength of association between these stimuli and the four target concepts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Living in a modern society also introduces a number of additional stressors associated with new challenges of the social reality that has emerged as a consequence of the Neolithic revolution, including those that did not exist in the ancestral environment where most human adaptations (including stress response) have evolved (Brenner et al, 2015;Katsampouris, Turner-Cobb, Barnett, & Arnold, 2020). The most essential of these shifts include change in diet and sleeping patterns, social organization (larger and more anonymous groups, less security of one's social position, less clear social roles, less certain career choice, the emergence of undesirable social/professional roles, etc.…”
Section: The New Perspectives Offered By the Evolutionary Argumentmentioning
confidence: 99%
“…Furthermore, not only are our social ecologies different from those inhabited by our ancestors (including, for example, dead-end jobs, utility payments, taxation, inefficient bureaucracies, etc. ), but they also engender the kinds of stressors that are less life-threatening but still use the same neurological mechanism by which the costly mobilization occurs (Hughes, Steffen, & Thayer, 2018;Katsampouris, Turner-Cobb, Barnett, & Arnold, 2020;Slavich, 2019). In other words, although the stress response is adaptive per se, its adaptive value (the payoff) is not present outside the ancestral environment 2 , thus potentially affecting the taxing task of keeping the balance between the problems that we have or have not adapted to solve (the 'evolutionary mismatch') (Brenner et al, 2015).…”
Section: The New Perspectives Offered By the Evolutionary Argumentmentioning
confidence: 99%